2015
DOI: 10.1007/s11082-015-0247-6
|View full text |Cite|
|
Sign up to set email alerts
|

Farbication of UV photodetector from nickel oxide nanoparticles deposited on silicon substrate by closed-field unbalanced dual magnetron sputtering techniques

Abstract: In this work, a UV photodetector was fabricated by depositing 25 nm nickel oxide nanoparticles on an n-type silicon substrate by a closed-field unbalanced dual magnetron sputtering technique. The fabricated photodetector showed maximum spectral responsivity of 4.8 mA/W at 318 nm with maximum quantum efficiency of 1.87 %. This is good attempt to produce such nanostructures with high quality and low cost for UV detection application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…This field causes traveling electrons to spiral along magnetic flux lines near the target instead of being attracted toward the substrate [5]. Magnetron sputtering (especially closed-field unbalanced magnetron configuration) has gained wide acceptance in both research and commercial purposes and is routinely used in different industries like cutting tools, forming tools, semiconductor, optical glass coating, decorative, biomedical, and tribology applications [6] glow discharge is simply produced by applying an electric potential on a gas sample between two electrodes placed inside a vacuum chamber .This glow discharge is a common source of plasma that can be established through an avalanche like ionization of gas neutrals at specific conditions for gas pressure and applied voltage [7]. Glow discharge plasma can generate in magnetron sputtering system, which are extensively used in various applications such as modification of surfaces [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…This field causes traveling electrons to spiral along magnetic flux lines near the target instead of being attracted toward the substrate [5]. Magnetron sputtering (especially closed-field unbalanced magnetron configuration) has gained wide acceptance in both research and commercial purposes and is routinely used in different industries like cutting tools, forming tools, semiconductor, optical glass coating, decorative, biomedical, and tribology applications [6] glow discharge is simply produced by applying an electric potential on a gas sample between two electrodes placed inside a vacuum chamber .This glow discharge is a common source of plasma that can be established through an avalanche like ionization of gas neutrals at specific conditions for gas pressure and applied voltage [7]. Glow discharge plasma can generate in magnetron sputtering system, which are extensively used in various applications such as modification of surfaces [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that the E g of a‐IZNO increases with increasing Ni content. The increased E g values can be attributed to the fact that NiO 2 has a larger bandgap (3.6–4.0 eV) than IZO (3.14 eV in this work) …”
Section: Resultsmentioning
confidence: 64%
“…The increased E g values can be attributed to the fact that NiO 2 has a larger bandgap (3.6-4.0 eV) than IZO (3.14 eV in this work). [18] Figure 4 shows AFM images of 35 nm-thick a-IZNO thin films deposited on SiO 2 /Si substrates. It can be seen that all a-IZNO thin films have smooth, crack-free surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Although, the device shows a modest responsivity, spectral response of the device is limited to UV region. In an another work, NiO-Si heterojunction is fabricated for UV detection which shows good responsivity [44]. However, the device fabrication involves expensive and sophisticated sputtering technique and also the usage of silicon renders it in-appropriate for flexible applications.…”
Section: Comparison With Similar Class Of Photodetectorsmentioning
confidence: 99%